Comprehensive profiling of Lingzhihuang capsule by liquid chromatography coupled with mass spectrometry-based molecular networking and target prediction. Issue 1 (22nd March 2022) - Huang, Mengliang; Yu, Sijia; Shao, Qing; Liu, Hao; Wang, Yingchao; Chen, Hongzhang; Huang, Yansheng; Wang, Yi
Abstract : Abstract: Objective: Lingzhihuang capsule (LZHC) is a natural product that consists of 10 commonly used medicinal plants, and it is used in traditional Chinese medicine to promote people's overall health. Previously, LZHC was successfully used as adjuvant therapy for treating patients with cancer. However, the chemical constituents of LZHC and their potential biological functions remain unclear. The aim of this study is to investigate the major bioactive compounds in LZHC and predict their pharmacological targets. Methods: The LZHC constituents were putatively identified by ultra-high performance liquid chromatography coupled with time-of-flight mass spectrometry combined with mass spectrometry-based molecular networking. The targets were predicted using SwissTargetPrediction software, and the associated gene ontology and Kyoto encyclopedia of genes and genomes pathways were analyzed using the Database for Annotation, Visualization, and Integrated Discovery. The mass spectrometry-based molecular network and compound-target-pathway network were constructed using Cytoscape 3.8.0 software. Results: We putatively identified 94 compounds of LZHC by mass spectrometry-based molecular networking, including triterpene (the main structural type) and other clusters (ie, flavonoids and organic acids). Our results suggested that multiple pivotal targets were regulated by LZHC, including tumor necrosis factor, nitric oxide synthase 2, glucocorticoid receptor, estrogen receptor, 3-oxo-5-alpha-steroid 4-dehydrogenase 2, prostaglandin e2 receptor ep4 subtype, estrogen receptor beta, phosphatidylinositol 4, 5-bisphosphate 3-kinase catalytic subunit alpha isoform, mitogen-activated protein kinase 3, and rac-alpha serine, which are related to signal transduction, positive regulation of transcription from RNA polymerase II promoters, oxidation-reduction processes, inflammatory responses, and other biological processes. Functional annotation of those targets suggested that several signaling pathways may be regulated by LZHC, such as cancer-related proteoglycans, the PI3K-Akt-signaling pathway, and the cAMP-signaling pathway. Conclusions: Our findings reveal the chemical constituents of LZHC and provided scientific support for the efficacy of LZHC in terms of immune regulation, anti-aging, and tumor suppression.